ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERNAL PENERIMAAN DAN PENGELUARAN KAS PADA PT ABC JAKARTA - Nawang Dyah Prameswari, - (2019)
This study aims to determine the suitability of the application of the internalcontrol system of cash receipts and disbursement applied to PT ABC Jakarta withinternal control standards according to COSO. Internal controls in intended includethe control environment, risk assessment, control activities, information and communication, and monitoring. This research uses a descriptive method withqualitative data that uses the interpretive paradigm and ethnomethodology approach. The results of this study indicate that application of internal control of cash receiptand disbursement in PT ABC Jakarta as a whole has referred to five (5) components of internal controls according to COSO and the role of actors in its in accordancewith the responsibilities of each actor. However, there are still some weaknesses such as the participation of the board of commissioners & audit committees, as well asinadequate organizational structures.